CREATIVE ECONOMY DEVELOPMENT FOR FORMER EAST TIMOR REFUGEES IN INDONESIA’S BORDER REGION: A CONCEPTUAL FRAMEWORK BASED ON LITERATURE AND POLICY ANALYSIS - Wida Ayu Puspitosari (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Despite receiving Indonesian citizenship in 2003, approximately 30,000 former East Timor conflict refugees in Belu Regency remain economically marginalized and face land insecurity and limited livelihood opportunities over two decades after displacement. Existing scholarship tends to examine refugee economic integration and creative economy development as separate domains, leaving a gap in understanding how creative industries might serve as systematic pathways for post-conflict integration in developing-country border regions with distinctive cultural assets. This study employs a qualitative, desk-based methodology integrating systematic literature review, policy document analysis from Indonesian government agencies and international organizations, and comparative case analysis of creative economy initiatives in post-conflict settings, including Colombia, Rwanda, Bangladesh, and Vietnam. The analysis identifies four complementary development pillars involving traditional crafts revival and market integration, cross-border cultural tourism, digital creative industries, and performing arts for social cohesion that structured into an integrated model tailored to Belu’s specific context of shared Tetum cultural heritage, transborder kinship networks, and emerging bilateral cooperation with Timor-Leste. Comparative evidence indicates that creative economy initiatives achieve greatest effectiveness when designed with genuine community ownership, conflict sensitivity, and realistic market linkage strategies. The proposed framework addresses systemic barriers including infrastructure deficits, financing constraints, and land tenure insecurity, and offers policy recommendations for coordinated implementation by government agencies, international organizations, and community-based institutions.